Epilepsy Board Review A Comprehensive Guide - Koubeissi, Mohamad Z.; Azar, Nabil J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2017)
This concise text mirrors the content of the Epilepsy Board as distributed by the American Board of Psychiatry and Neurology. Epilepsy diagnosis, classification and treatment are thoroughly covered, along with seizure classification, epidemiology, normal and abnormal EEG, and treatment with antiepileptic medications and other modalities. Formatted with multiple choice questions and explanations, this complete resource will prepare physicians and students for the Epilepsy Board examination and provide the latest clinical approaches.
Ch. 1: Physiologic Basis of EEG and Epilepsy -- Ch. 2: EEG instrumentation, Montage, Polarity, and Localization -- Ch. 3: Normal EEG Variants and Artifacts -- Ch. 4: Neonatal EEG and Neonatal Seizures -- Ch. 5: MCQ -- Ch. 6: Ictal and Interictal EEG -- Ch. 7: EEG and Semiology in Generalized Epilepsies -- Ch. 8: EEG and Semiology in Focal Epilepsy -- Ch. 9: Status Epilepticus -- Ch. 10: EEG in Encephalopathy and Coma -- Ch. 11: MCQ -- Ch. 12: Electro-clinical Syndromes by Age of Onset - Childhood, Adolescence-adult -- Ch. 13: Seizures and Epilepsy in Early Life -- Ch. 14: Imitators of Epilepsy -- Ch. 15: Genetic Analysis of Epilepsies -- Ch. 16: Epilepsy Secondary to Specific Mechanisms -- Ch. 17: MCQ -- Ch. 18: Principles of Epilepsy Diagnosis and Management -- Ch. 19: Old Generation Antiepileptic Drugs -- Ch. 20: New Generation Antiepileptic Drugs -- Ch. 21: Dietary Therapies -- Ch. 22: Other Pharmacological Therapies: Investigational Antiepileptic Drugs, Animal Models of Epilepsy, Hormonal Therapy, Immunotherapy -- Ch. 23: Epilepsy Management in Special Populations -- Ch. 24: MCQ -- Ch. 25: Neuroimaging in Epilepsy -- Ch. 26: Neuropsychological Evaluation in Epilepsy -- Ch. 27: Magnetoencephalography and magnetic source modeling -- Ch. 28: Vagus Nerve Stimulation and other Neuromodulation -- Ch. 29: Epilepsy surgery assessment and testing -- Ch. 30: Procedures and outcomes in epilepsy surgery -- Ch. 31: Quality of Life in Epilepsy -- Ch. 32: MCQ.
Keywords: Medicine; Neuroradiology; Neurology; Neurosurgery; Medicine & Public Health; Neurology; Neurosurgery; Neuroradiology